2018
DOI: 10.15253/2175-6783.2018193322
|View full text |Cite
|
Sign up to set email alerts
|

Interações medicamentosas induzidas pelo aprazamento e os erros no preparo de antibacterianos

Abstract: Objetivo: identificar as interações medicamentosas induzidas pelo aprazamento e os erros no preparo de antibacterianos administrados. Métodos: estudo observacional e transversal, realizado em clínicas médicas de hospital da rede sentinela. A coleta de dados ocorreu por meio da observação das prescrições e do preparo de 265 doses de antibacterianos com a utilização de um check-list. Resultados: prevaleceu a administração da Piperaciclina e Tazobactan, com 51 doses. O aprazamento de horário dos antibacterianos c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…Pereira et al, 2018a 14 Identificar interações medicamentosas induzidas pelo aprazamento e os erros no preparo de antibacterianos administrados.…”
Section: Autor Objetivo Tipo De Estudo Principais Resultadosunclassified
See 2 more Smart Citations
“…Pereira et al, 2018a 14 Identificar interações medicamentosas induzidas pelo aprazamento e os erros no preparo de antibacterianos administrados.…”
Section: Autor Objetivo Tipo De Estudo Principais Resultadosunclassified
“…As principais não conformidades identificadas foram doses errôneas e atrasos na administração de antimicrobianos [14][15][16][17][18] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Other studies relate the scheduling practice to the occurrence of drug interactions and MEs, which draws the attention to a more accurate survaillance regarding the medication administration times. 47,48 Among the safety requirements, another fact that should be highlighted is the identification of patients, both on the bed or on the bracelet and by the professional during administration. At the local study hospital, it was observed that 12.1% of the patients were unidentified, associated with the infant age group, and that 94.3% of the nursing technicians/assistants did not perform patient identification at the time of administration.…”
Section: Types Of Prescription Errors N (%) Types Of Administration Ementioning
confidence: 99%
“…It is reiterated that several studies have pointed to factors responsible for errors during the process, including lack of knowledge about medicines by professionals and outdatedness regarding active principles; lack of control and standardization of procedures in the preparation; similar names and packaging colors of medicinal products; lack of alerts in the system to signal the occurrence of errors; and a poorly organized environment. [11][12][13] It was noted during the data collection that all prescriptions were checked before administration of the medicines. This attitude on the part of the team agrees with the literature, which emphasizes the importance of checking the characteristics in the prescription before carrying out any administration.…”
Section: Itmentioning
confidence: 99%